Ergasiophytes of old cemeteries of the Right-Bank of Dnipro Grass Steppe District (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Questions: What is the species richness, diversity of life forms of ergasiophytes of old cemeteries of the Right-Bank of Dnipro Grass Steppe District? How does the species richness and diversity of life forms of ergasiophytes vary depending on their location in an urbanized environment? Locations: Right-Bank of Dnipro Grass Steppe District (Ukraine) Materials and methods: field observations and herbarium collections Nomenclature: A checklist of vascular plants, bryobionts, and lichens of Ukraine for storing vegetation plots in TURBOVEG (Vynokurov et al. 2025) Results: Every year, the number of ergasiophytes is significantly increases at cultural heritage sites and old cemeteries. The results of comprehensive study on ergasiophytes in the alien fraction of the flora of old cemeteries of the Right-Bank of Dnipro Grass Steppe District are presented. Ergasiophytes include 119 species from 101 genera and 48 families of vascular plants, which is 17.3 % of the spontaneous flora of old cemeteries. The group of ergasiophytes is the most numerous group in terms of the degree of naturalization in the alien flora of old cemeter-ies. A high proportion of ergasiophytes is a characteristic feature of the flora of old cemeteries compared to other cultural heritage sites, including kurgans and ancient settlements. The largest representation of ergasiophytes is observed in old cemeteries located in cities (17.2 %), slightly inferior to them in this indicator are rural cemeteries (16.3 %), while cemeteries located far outside of settlements are characterized by a small participation of ergasiophytes (7.3 %). In addition, old cemeteries closed for burial have twice the percentage of ergasiophytes (8.3 %) compared to active cemeteries (16.8 %). In the spectrum of life forms among ergasiophytes, there is a very high proportion of phanerophytes (39.5 %), especially when compared to natural zonal flora. The sponta-neous spread of trees and shrubs from cultivation sites leads to the dis-placement of steppe plants in cemeteries and outside them, so it is neces-sary to control their spread.
Keywords: biodiversity, steppe, cultural heritage objects, old cemeteries, alien species, Ukraine